PEMBERIAN PENGUATAN GURU DALAM PEMBELAJARAN FIQIH DI MINIKOM (PRAKOM MINI) PP. MAMBAUL ULUM BATA-BATA - Latifatul Mahbubah; Miftahusurur Assiddiqi; Moh Faiz (Tarbawi, 2023)
AbstractThe strengthening or reinforcement is a response to student behavior that can increase the likelihood of that behavior recurring. Verbal reinforcement involves expressions using words of praise, appreciation, approval, and the like, while nonverbal reinforcement includes body language, touch, giving rewards, and similar actions by a teacher. This study aims to understand the forms of teacher reinforcement towards students in the Islamic jurisprudence (fiqh) lesson at MINIKOM (mini practice) of the Mambaul Ulum Bata-bata Islamic Boarding School. The research employs a qualitative research method with a case study approach. The results indicate that the verbal reinforcement components used by teachers in teaching fiqh at MINIKOM of the Mambaul Ulum Bata-bata Islamic Boarding School include declarative, imperative, and interrogative forms, while the nonverbal reinforcement by teachers in fiqh at MINIKOM of the Mambaul Ulum Bata-bata Islamic Boarding School consists of facial expressions, approaching students, and body movements. Keywords: Reinforcement, fiqh learning.AbstrakPenguatan atau reinforcement merupakan respon terhadap prilaku siswa yang dapat meningkatkan kemungkinan terulangnya kembali perilaku tersebut. Penguatan verbal adalah ungkapan dengan menggunakan kata-kata pujian, penghargaan, persetujuan dan sebagainya sedangkan penguatan nonverbal adalah gerak badan, sentuhan, memberi hadiah dan semacamnya dari seorang guru. Penelitian ini bertujuan untuk mengetahui bentuk penguatan guru kepada siswa pada pelajaran fiqih di MINIKOM (prakom mini) Pondok Pesantren Mambaul Ulum Bata-bata. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Hasil penelitian ini menjunjukkan bahwa komponen penguatan verbal guru dalam pembelajaran fiqih di MINIKOM Pondok Pesantren Mambaul Ulum Bata-bata adalah bentuk deklaratif, imperatif, dan introgatif, sedangkan penguatan nonverbal guru dalam fiqih di MINIKOM Pondok Pesantren Mambaul Ulum Bata-bata adalah bentuk facial, mendekati siswa, dan gerak badan.Kata kunci: Pemberian penguatan, pembelajaran fiqih.